The Meaning and Values of Pahangga as a Representation of The Identity and Image of Gorontalo City - Fitriani, Dara; Hatta, Asta Juliarman; Abdul, Nurnaningsih Nico (Sinektika: Jurnal Arsitektur, 2025)
Gorontalo, a city rich in history and culture, has many elements of traditional architecture that serve as symbols of the identity and cultural heritage of its people. One important element in Gorontalo's traditional architecture is the Pahangga. Although previous research has discussed Gorontalo’s traditional architecture, limited studies have explored how Pahangga can be adapted in contemporary architecture while preserving its symbolic meaning. This study aims to explore the meaning and value of Pahangga as a representation of the identity and image of Gorontalo City. Pahangga, which is an ornament of Gorontalo culture, has a deep history and meaning in local culture. The method used is a descriptive qualitative approach with a semiotic approach, which analyzes signs and symbols to explore the philosophical meaning and cultural values contained in the Pahangga elements. The results of the study show that Pahangga has been used as a decorative element in various public buildings, such as school gates, city parks, and boundary gates. Pahangga not only has a symbolic meaning related to social hierarchy and cultural values, but also plays a role in shaping the identity and visual image of the city. This study concludes that Pahangga has great potential to be strengthened as an element that forms the identity and image of Gorontalo City through wider application to urban elements such as pedestrian paths and landmarks. Thus, the contributions and practical implications are expected to be a guide for city planners such as architects, urban planners, and parties involved in adopting local cultural elements as part of efforts to create inclusive, iconic, and culturally meaningful public spaces amidst city modernization.